Prevalence of Drug-Related Problems in Elderly Cancer Patients: A Prospective Observational Study in a Cancer Specialty Hospital - Paul, Acsah Annie; Ramesh, Madhan; Srinivas, KG (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: The geriatric population comprises the majority of patients with oncological disorders. They are highly vulnerable to drug-related problems (DRPs) due to multiple comorbidities, polypharmacy, altered pharmacokinetics and pharmacodynamics. This study aimed to determine the rate and pattern of drug-related problems in elderly cancer patients. Materials and Methods: A observational study was conducted prospectively for a period of 4 months, where cancer patients of any gender above 60 years were enrolled and followed daily. All necessary data like patient demographics, past and current medication history were obtained from various data sources including medical records, treatment charts, patient interviews etc. DRPs were identified and assessed. Results: A total of 50 patients were enrolled into the study. From which, 96 DRPs were identified among 74% of the patients. Commonly observed DRPs were Adverse Drug Reactions (40%) and Drug-Drug Interactions (20.8%). More than half of the patients who developed DRPs (67.6%) had comorbidities, 86% were currently on chemotherapy alone or in combination and majorly (81%) were in the advanced cancer stage (Stage III and stage IV). Hyper polypharmacy was observed in 67.6% of the patients with DRPs. Conclusion: Our study revealed that DRPs are highly prevalent amongst elderly cancer patients and geriatric cancer patients need careful follow-up to identify DRPs and reduce adverse outcomes.
Keywords: Drug-related problems; Geriatric oncology; Cancer; Polypharmacy